Making extraordinary things happen in Asia applying the five practices of exemplary leadership - Kouzes, James M. (Jossey-Bass, 2013)
An in-depth look at how leaders in Asia apply the Five Practices of Exemplary Leadership in their organizations Kouzes and Posner's Five Practices of Exemplary Leadership is the most trusted and proven leadership paradigm in the business world.